Randomized comparison between epidural waveform analysis through the needle versus the catheter for thoracic epidural blocks. Issue 8 (14th May 2019) - Tangjitbampenbun, Amornrat; Layera, Sebastián; Arnuntasupakul, Vanlapa; Apinyachon, Worapot; Venegas, Karen; Godoy, Jaime; Aliste, Julián; Bravo, Daniela; Blanch, Alonso; Webar, Javier; Saadawi, Mohammed; Owen, Andrew; et al.
Abstract : Background: Epidural waveform analysis (EWA) provides a simple confirmatory adjunct for loss of resistance (LOR): when the needle/catheter tip is correctly positioned inside the epidural space, pressure measurement results in a pulsatile waveform. Epidural waveform analysis can be carried out through the tip of the needle (EWA-N) or the catheter (EWA-C). In this randomized trial, we compared the two methods. We hypothesized that, compared with EWA-C, EWA-N would result in a shorter performance time. Methods: One hundred and twenty patients undergoing thoracic epidural blocks for thoracic or abdominal surgery were randomized to EWA-N or EWA-C. In the EWA-N group, LOR was confirmed by connecting the epidural needle to a pressure transducer. After obtaining a satisfactory waveform, the epidural catheter was advanced 5 cm beyond the needle tip. In the EWA-C group, the epidural catheter was first advanced 5 cm beyond the needle tip after the occurrence of LOR. Subsequently, the catheter was connected to the pressure transducer to detect the presence of waveforms. In both study groups, the block procedure was repeated at different intervertebral levels until positive waveforms could be obtained (through the needle or catheter as per the allocation) or until a predefined maximum of three intervertebral levels had been reached. Subsequently, the operator administered a 4 mL test dose of lidocaine 2% with epinephrine 5 µg/mL through the catheter. An investigator present during the performance of the block recorded the performance time (defined as the temporal interval between skin infiltration and local anesthetic administration through the epidural catheter). Fifteen minutes after the test dose, a blinded investigator assessed the patient for sensory block to ice. Success was defined as a bilateral block in at least two dermatomes. Furthermore, postoperative pain scores, local anesthetic consumption, and breakthrough analgesic consumption were recorded. Results: No intergroup differences were found in terms of performance time, success rate, postoperative pain, local anesthetic requirement, and breakthrough analgesic consumption. Conclusion: EWA can be carried out through the needle or through the catheter with similar efficiency (performance time) and efficacy (success rate, postoperative analgesia). Trial registration number: NCT03603574 .